2009
DOI: 10.1590/s0100-83582009000500023
|View full text |Cite
|
Sign up to set email alerts
|

Fitotoxicidade de herbicidas a diferentes cultivares de milho-pipoca

Abstract: 4RESUMO -Com o objetivo de avaliar a seletividade de diferentes herbicidas a dez genótipos de milho-pipoca em Campos dos Goytacazes-RJ, realizou-se a aplicação de herbicidas em dosagem máxima recomendada (atrazine + S-metolachlor + extravon -1,665 + 1,035 kg ha -1 i.a. + 0,1%; foramsulfuron + iodosulfuron + hoefix -45,0 + 3,0 g ha -1 i.a. + 0,5%; mesotrione + óleo mineral -192 g ha -1 + 0,5%; tembotrione + óleo mineral -240 mL ha -1 + 0,5%) e um tratamento sem aplicação de herbicida, em esquema fatorial 5 x 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…For the evaluation of phytotoxicity the adapted scale from [10,11,12] was used, with 0 = for absence of phytotoxicity; 1–25 = light chlorosis or beginning of necrosis on the seedlings leaves; 26–50 = medium chlorosis or necrosis on the seedlings leaves; 51–75 = high chlorosis or necrosis on the seedlings leaves; and 76–100 = wilt and dryness of the plant.…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluation of phytotoxicity the adapted scale from [10,11,12] was used, with 0 = for absence of phytotoxicity; 1–25 = light chlorosis or beginning of necrosis on the seedlings leaves; 26–50 = medium chlorosis or necrosis on the seedlings leaves; 51–75 = high chlorosis or necrosis on the seedlings leaves; and 76–100 = wilt and dryness of the plant.…”
Section: Methodsmentioning
confidence: 99%
“…In the IAC -125 hybrid and in the UENF-14 variety, the value of Fv/Fm did not change with the application of tembotrione during the period of evaluation, and, regarding the nicosulfuron, there was no change in the values of Fv/Fm for any cultivars. Freitas et al (2009) observed that the tembotrione caused slight toxicity, in post-emergence, the more affected popcorn varieties were PA-038 (with 50% of phytotoxicity) and Viçosa-Maringá (with 18,75% phytotoxicity), but both presented fast recovery. Cavalieri et al (2008) did not observe effect on productivity due to nicosulfuron in corn hybrids, noting however that some hybrids showed phytotoxicity symptoms occurring differential tolerance among these being necessary steps to evaluate this tolerance yield.…”
Section: Resultsmentioning
confidence: 93%
“…Due to the limited information about selective herbicides for popcorn cultivation, many farmers improperly use products registered for common corn, which may not be selective to some varieties of popcorn corn (Freitas et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Each vase was pulverized with 5 mL of the solutions. The evaluation was made according to the phytotoxicity scale adapted from [12] until the tenth day.…”
Section: Methodsmentioning
confidence: 99%